Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution - Li, Zhu; Yang, Ding; Murphy, William L. (Zootaxa, 2019)
The status of the 20 genera comprising at least 60 species of Sciomyzidae known from China is reviewed. Ten genera are recorded for the first time from China. A diagnostic key to all genera known from China is provided along with figures of the main characters. The geographic distribution of every genus known from China is discussed and distribution maps are presented. Recorded for the first time in the Oriental Region are 2 genera (Coremacera Rondani, 1856 and Pherbina Robineau-Desvoidy, 1830) and 5 species (in Dichetophora Rondani, 1868, Pherbellia Robineau-Desvoidy, 1830, and Tetanocera Duméril, 1800). Euthycera meleagris Hendel, 1933, previously synonymized with Dichetophora meleagris (Hendel, 1933), is resurrected as a valid name. Pherbellia brevistriata Li, Yang & Gu, 2001 is placed as a junior synonym of Pherbellia nana reticulata (Thomson, 1869). Reported for the first time are the female of Pherbellia ditoma Steyskal, 1956 and the male of Pherbellia orientalis Rozkošný & Knutson, 1991, both discovered in China during this study.